Ketahanan Energi Rusia dan Kerentanan Pasar Asia-Pasifik - M Faris Alfadh (Department of International Relations, Universitas Andalas)
This paper attempts to explain Russia’s energy security untill the next decade, and its impact on energy security of the Asia-Pacific region. As the world’s largest natural gas reserves and the second largest producer of crude oil, Russia is very important to the world energy markets. But for Russia, energy is not merely as a driving factor for its economic growth, but also as a political forse in its international relations. Russia’s ambitions are to become the world’s largest energy producer and the most influential to the world energy market. In this case, the Asia-Pacific region becomes important given the huge market potential. However, Russia’s energy security policy does not have entirely a positive impact on the stability of energy supply in the Asia-Pacific region. The market vulnerability and unfair competition among countries in the Asia-Pacific region will increase along with the Russia’s energy security policy.